Mali : Sixth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Request for Waivers of Nonobservance of Performance Criteria and Request for Extension of Commitment Period; Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Mali. (IMF Staff Country Reports; Country Report ;, 2008)
On the basis of the authorities' record and actions, IMF staff supports the authorities' request for waivers of two structural performance criteria and one quantitative performance criterion and completion of the sixth review. The authorities completed most of their ambitious structural reform agenda for the sixth poverty reduction growth facility (PRGF) review, albeit with some delays. To enhance the efficiency and soundness of the financial sector and boost growth, the authorities completed a new financial sector development strategy in October, in cooperation with the IMF and the World Bank.